ARTISTIC GYMNASTICS AND FEAR: REFLECTIONS ON ITS CAUSES - Duarte, Luiz Henrique [UNESP]; Carbinatto, Michele Viviene; Nunomura, Myrian [UNESP] (Univ Ljubljana, Fac Sport, 2015)
In the field of sports psychology it is nearly unanimous that both positive and negative emotions directly affect sports performance. In the case of artistic gymnastics (AG), it is not uncommon for athletes to face one specific, characteristic emotion: fear. In this study, we will conduct an analysis of fear felt by gymnasts in training in order to detect subjective perceptions about the causes of fear and the strategies utilized to control it. Sixteen gymnasts who compete in the pre-infantil (9 - 10 years) category of the Sao Paulo State Championship were interviewed. Content analysis was selected as the methodological technique for data. We detected four units of registry for analyzing the causes of fear: fear of injury, fear of error, fear of apparatus and fear of coach. Regarding strategies for controlling fear, we detected seven units: social support (friends and family), instructional support, attention and concentration, positive thinking and self-confidence, mental practice, and relaxation techniques. In general, coaches can interfere as much in the manifestation of fear as in its control. Among possible pedagogical strategies, we can highlight adjustments to the training environment and instructional procedures that facilitate the teaching-learning process, particularly in regards to the athletes' feelings of security.
Keywords: gymnasts; sport; competition; emotion; psychological approach; qualitative research